The association of cardiovascular disease with impaired health-related quality of life among patients with type 2 diabetes mellitus - Tan, Mun Chieng; Ng, Ooi Chuan; Wong, Teck Wee; Abdul Rahman, Hejar; Anthony, Joseph; Sintonen, Harri (Singapore Medical Association, 2014)
INTRODUCTION The aim of this study was to evaluate the health-related quality of life (HRQoL) of Malaysian patients with type 2 diabetes mellitus (T2DM) who have cardiovascular disease (CVD), as well as identify the determinants of HRQoL among this cohort of patients. METHODS This study was an analytical cross-sectional study involving 313 patients aged 30–78 years (150 men, 163 women; mean age 55.7 ± 9.2 years) who were diagnosed with T2DM (mean duration of T2DM 10.1 ± 8.1 years) at two tertiary Malaysian government hospitals. The patients’ sociodemographic, lifestyle, clinical and laboratory data were collected prospectively from medical records and via face-to-face interviews. HRQoL was assessed using the 15D instrument – a generic, 15-dimensional and standardised measure of HRQoL that can be used as both a profile and a single index score measure. RESULTS T2DM patients with CVD were found to have significantly lower 15D HRQoL scores than their non-CVD counterparts (p < 0.001). The HRQoL of T2DM patients with CVD was significantly lower than those without CVD (p < 0.05) in all of the 15 dimensions of the 15D instrument. Multinomial logistic regression analysis using backward stepwise method revealed a significant association between CVD and impaired HRQoL (odds ratio [OR] 11.746, 95% confidence interval [CI] 4.898–28.167). Age (OR 1.095, 95% CI 1.054–1.137), duration of T2DM (OR 1.085, 95% CI 1.032–1.140), ethnicity (OR 0.411, 95% CI 0.187–0.903), body mass index (OR 1.074, 95% CI 1.006–1.148), and physical activity level (OR 3.506, 95% CI 1.415–8.689) were also significant predictors of HRQoL. CONCLUSION In T2DM patients, the presence of CVD was significantly associated with a lower HRQoL. Therefore, the importance of tertiary prevention to minimise the potential deterioration of the HRQoL of T2DM patients with CVD should be highly emphasised.